1988
DOI: 10.1016/s0022-5347(17)42041-6
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Metabolism in Pheochromocytoma and Normal Adrenal Medullae

Abstract: The tissue contents of catecholamine, its precursor and its major metabolites were determined in 8 human pheochromocytomas and 26 normal adrenal glands. Pheochromocytomas contained significantly larger amounts of norepinephrine, dopamine, dihydroxyphenylalanine, tyrosine hydroxylase activity, metanephrine, normetanephrine and vanillylmandelic acid than did normal adrenal medullae. The content ratio of epinephrine/norepinephrine in normal adrenal medullae was significantly higher than that in pheochromocytomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This was ruled out as this type of feedback has not been described in phaeochromocytoma in which secretion and liberation of catecholamines appear to be out of control. 10 We assumed it to have been due to saturation of a-1 receptors by urapidil, which would lead to an increase in the amounts of circulating norepinephrine. This increase in the area under the curve of norepinephrine was interpreted as a pharmacological validation of optimal blockade of a-1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This was ruled out as this type of feedback has not been described in phaeochromocytoma in which secretion and liberation of catecholamines appear to be out of control. 10 We assumed it to have been due to saturation of a-1 receptors by urapidil, which would lead to an increase in the amounts of circulating norepinephrine. This increase in the area under the curve of norepinephrine was interpreted as a pharmacological validation of optimal blockade of a-1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Nakada et al (19) reported that pheochromocytomas contained a significantly larger amount of catecholamines and greater tyrosine hydroxylase activity than did normal adrenal medullas. Iwase et al (20) also observed high tyrosine hydroxylase activity in pheochromocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of tyrosine hydroxylase, aromatic L-amino acid decarboxylase and dopamine ß-hydroxylase are generally very high in these tumors, providing the basis for catecholamine overproduction in these tumors (62-64). Among different pheochromocytomas, activities of tyrosine hydroxylase are high in tumors from patients with MEN2 and low in those from von Hippel-Lindau (VHL) patients or patients with non-functional tumors (57, 58).…”
Section: Pheochromocytoma: a Catecholamine Disordermentioning
confidence: 99%